Extração e exportação de nutrientes pelo híbrido de mamona Savana: I – macronutrientes - Costa Crusciol, Carlos Alexandre [UNESP]; do Nascimento, Martha Santana [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Zanotto, Maurício Dutra [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Low height castor bean hybrids and highly productive possibly need larger quantity of macronutients during its development cycle. However, in Brazil there is little information on extraction and exportation of macronutrients by low height castor bean hybrids, as on season as out-of-season growing. This study aimed to evaluate the nutrients extraction and exportation by Savana hybrid castor bean on season and out-of-season growing. The experiments were conducted during the season of 2005/2006 and out-of-season of 2006 in an Oxisol. The experimental design was a randomized block with four replications. The plots were consisted by harvest times of plants, which were composed by six plant rows to 5 m, spaced 0.45 m between rows. Samples were collected at 17, 31, 45, 59, 73, 97 and 120 days after emergence (DAE) during the season and at 17, 31, 45, 59, 80; 100 and 120 DAE in the out-of-season. The nutrients accumulation by Savana hybrid was small until the flowering (30 DAE), but intensified after this period. The period of greatest nutrient absorption occurred at 65 and 90 DAE for N, 70 and 80 DAE for P, 60 DAE for K and Mg, 55 and 60 DAE for Ca and S. The amounts absorbed per hectare by hybrid Savana ranged 155 to 31 kg of N, 17 to 3 kg of P, 71 to 13 kg of K, 56 to 12 kg of Ca, 28 to 4 kg of Mg and 29,5 to 7 kg of S in season and out-of-season, respectively. The yield was higher in growing season, but the nutrients extraction and exportation per ton of grain were similar among the seasons. Among 40% and 50% of N and S and most part of Mg, K and Ca accumulated in the plants returned to soil with crop residues, but less than 35% of P remained in the residues.
Nutrients extraction and exportation by Savana castor bean hybrid: I - macronutrients
Keywords: Ricinus communis; mineral nutrition; absorption curves; absorption rates; yield